معالم التفسير المقاصدي للقرآن الكريم :‏ ‏آيات الخمر نموذجا /‏ - خالد، نشوان بن عبده (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This research attempts to outline features of al-tafsir al-maqasidi (motif-orented exegesis) of the Holy Quran. It aims to provide an appropriate definition for it, show it differs from other types of exegesis, and subsequently apply the concepts to one particular case, namely the prohibition of intoxicants. This is carred out by examning the verses related to the prohibition of intoxicants wich were revealed in stages rather than at once. This indeed cotributed tremendously to a major change in th social dimension of the society at that time, wich actually shows the Islamic approach in effecting change in a social reality. Here a link is established between what actually took place and the attention to the motif established from the verses in point. In addition, the researcher tries to clarify the link between the prohibition of intoxicants and the honouring of mind in Islam through the discussion on the importance of the intellect (al-aql), the Quran motif of ensuring its functionality, the harms that result from consuption of intoxicants and the role accorded to it (the intellect) in light of the Quranic motifs.The researcher uses an inductive approach for gathering materials relevant to this topic, and then analyzes those materials to infer the motifs and goals. The researcher concludes that the objectives of the Holy Quran represent the fundamentals of Islam and basis for relevant legislation and the Islamic ummah should agree upon, in order to pave the way for better coexistence among the various faction of the ummah, especially in this age where those fundamentals and motifs are rather ignored as unifying factors whilst they are precisely the factors that would lead to stability and harmony in various aspects of life.